General practitioners’ knowledge, attitudes, beliefs, and practices in the management of sexual dysfunction : results of the portuguese SEXOS study - Alarcão, Violeta (2012)
© 2012 International Society for Sexual Medicine - The definitive version is available at www3.interscience.wiley.com